1987
DOI: 10.1210/jcem-64-3-425
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone (GnRH)-Binding Sites in Human Breast Cancer Cell Lines and Inhibitory Effects of GnRH Antagonists*

Abstract: GnRH-binding sites have previously been described in human breast tumors, and a GnRH agonist has been shown to inhibit growth of the MCF-7 human breast cancer cell line. We have investigated the presence of GnRH-binding sites in ZR-75-1, MDA-MB-231, Sk Br 3, MDA-MB-157, and MCF-7 human breast cancer cell lines and the effect of GnRH analogs on the incorporation of [3H]thymidine and 14C-labeled amino acids into DNA and protein. Specific GnRH-binding sites were present in membrane preparations of all five human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
1
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(122 citation statements)
references
References 14 publications
10
109
1
2
Order By: Relevance
“…The presence of GnRH receptors in breast cancer tissue [31] and the demonstration of antiproliferative actions of GnRH analogs in breast cancer cell lines [32,47,96] supported this interpretation. Antiproliferative effects of GnRH analogs and the expression of GnRH receptors have now been demonstrated in a number of cell lines of reproductive tract tumors, including prostate, uterine and ovarian cancers, and also in nonreproductive tract tumors [21,43,47,70,73,79].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 84%
See 1 more Smart Citation
“…The presence of GnRH receptors in breast cancer tissue [31] and the demonstration of antiproliferative actions of GnRH analogs in breast cancer cell lines [32,47,96] supported this interpretation. Antiproliferative effects of GnRH analogs and the expression of GnRH receptors have now been demonstrated in a number of cell lines of reproductive tract tumors, including prostate, uterine and ovarian cancers, and also in nonreproductive tract tumors [21,43,47,70,73,79].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 84%
“…15). A number of antagonists of gonadotrope GnRH receptors act as GnRH agonists in the inhibition of tumor cell lines [32,34,44,81,128].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 99%
“…Only low-affinity binding could be demonstrated (Fig. 3) failed to demonstrate high-affinity binding of GnRH to noncarcinogenic mammary tissue [21,22]. It was suggested that this discrepancy might be due to activation of some genes as a result of carcinogenic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In both reports, the extrapituitary GnRH receptor transcripts were found to have nucleotide sequence identical with that of the pituitary gland. Although GnRH analogs have been demonstrated to exhibit direct effects on growth rate of MCF-7 cells [3,4,24], the affinity and even the detection of specific binding sites for GnRH in this cell line is still a matter of controversy [21,22,24]. Heterogeneity of receptors has been recognized to be an efficient way for obtaining different biological responses to a single hormone stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…3 LH-RH receptors also have been demonstrated in estrogen-independent MXT mouse mammary tumor 5,6 and in many human breast carcinoma cell lines. [7][8][9][10] In the past decade, various cytotoxic LH-RH analogs have been synthesized in our laboratory. 11 These hybrids consisted of various cytotoxic agents linked to LH-RH agonists or antagonists.…”
mentioning
confidence: 99%